a) -4+(-3):[2-(3)]+1=-4+(-3):(-1)+1=-4+3+1=0
b) 3-2×{5-3[4-(+2)]}=3-2×{5-3[2]}=3-2×(-1)=5
c) -2×[3-(-6)²:(-9)]-2×[12]=-2×[3-36:(-9)]-24=-2×[3-(-4)]-24=-2×7-24=-14-24=-38
d)-5²+3:[7-3]=-25+3:4=(-25×4+3):4=-13/4
e) -8-4-(-6)×1=-12+6=-6
f). 5[2³-14-(-5)]=5×[8-14+5]=5×(-1)=-5
g) ( -3)³-8+125=-3-8+125=-11+125=114
h). -8×(-4)-9×[2-3×2]=32-9×(-4)=32+36=68
i) 3-l-5l:(2-7)= 3-5:(-5)=3+1=4
j) -4-l4:( 3-1)=-4-4:2=-6
Sper ca te-am ajutat, dar am o mare rugaminte: sa nu mai folosesti niciodata "ajutatima" ci asa cum este corect AJUTATI-MA